A Longitudinal Study of Perceived Ethics Among Business Students - McKinzie, Kaye; Chen, Alexander; Rubach, Michael; Carson, Marsha (Journal of Leadership, Accountability and Ethics, 2022)
This study examines perceptions of ethical behavior based on surveys conducted over 35 years (1985 to 2020). The original research is based on questions presented to students in 1985 and 2001 (Emerson and Conroy, 2004). The authors used 25 vignettes in that study and surveyed at a large, private, religiously affiliated university. Several other researchers have used a subset of these same 25 vignettes to better understand student attitudes toward ethical issues within the corporate context. Our study compares a 10- question subset over time at multiple locations. These scenarios are divided into constructs for comparison to see if there is a time-based trend. The presupposed general trend is that students’ ethics have improved. This study reports on statistical differences by year over time and on individual questions and themes. We find support for our hypothesis that ethics have improved in some instances, but the findings are mixed. The review of the constructs and individual questions should aid colleges and universities in identifying the strengths and weaknesses in their ethics curricula.